2019
DOI: 10.3389/fphar.2019.01467
|View full text |Cite
|
Sign up to set email alerts
|

Polygonum multiflorum-Induced Liver Injury: Clinical Characteristics, Risk Factors, Material Basis, Action Mechanism and Current Challenges

Abstract: Polygonum multiflorum Thunb. (PM), called Heshouwu in China, is a popular Chinese medicine in clinical practice. Several clinical studies have been conducted to evaluate the traditional therapeutic claims and to study the potential therapeutic activity of PM in dyslipidemia and neurodegenerative diseases, highlighting available clinical evidence. In recent years, reports on clinical adverse reactions of Raw Radix P. multiflorum (RPM) and P. multiflorum Praeparata (PMP) have been on the increase, especially wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 147 publications
1
21
0
Order By: Relevance
“…So far, there are several retrospective analysis studies investigating the clinical cases on RPM induced liver injury [ 59 , 60 , 61 ]. According to these studies, the common reasons for consuming RPM products included treating grey hair, hair loss, using it as a health supplement, or for the treatment of hypertension, coronary heart disease, hyperlipidemia, etc.…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there are several retrospective analysis studies investigating the clinical cases on RPM induced liver injury [ 59 , 60 , 61 ]. According to these studies, the common reasons for consuming RPM products included treating grey hair, hair loss, using it as a health supplement, or for the treatment of hypertension, coronary heart disease, hyperlipidemia, etc.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…Most of the liver injuries induced by RPM were diagnosed as hepatocellular injury followed by mixed liver injury and cholestatic liver injury with jaundice, fatigue, anorexia as the major symptoms of RPM induced liver injury. Although RPM can induce liver injury in different degrees and even lead to death, the majority of RPM associated liver damage was found to be reversible after discontinuing RPM products and conservative care [ 59 , 60 , 61 ].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…As outlined in the report of Chau et al, 20 the interrater agreement between experts and RUCAM was 81%, facilitating evaluations and exclusion of cases with alternative causes or unclear herbal product identification. In general, RUCAM-based HILI series are preferred that cover in more detail a single herb, such as Gynura segetum and other pyrrolizidine alkaloids (PAs)-containing herbs like in the reports of Lin et al 21 and Gao et al, 22,25 or Psoralea corylifolia like in the reports of Cheung et al 19 and Li et al, 34 or Polygonum multiflorum (PM), as shown in the reports of Dong et al, 23 Wang et al, 27 Zhu et al, 28 Li et al, 31 Jing et al, 33 and Liu et al 35 For instance, Li et al 31 presented a perfect case report on HILI caused by PM, using the updated RUCAM of 2016. 15 Similarly, the case series of Dong et al 23 focuses on PM on a single herb causing HILI in 18 patients, with each having received an individual causality grading of probable or highly probable.…”
Section: Chinamentioning
confidence: 97%
“…Occasionally, RUCAM-based causality gradings, classified initially as possible, had afterwards been upgraded to a probable level through a non-transparent maneuver 36 -an overall highly questionable and disputable approach as also discussed previously. 11 In rare instances, causality gradings were not reported 35 or RUCAM was used for causality grading but the respective publication remained unquoted, 26,34 even if the updated RUCAM was mentioned in the text. 34 Similar omissions of RUCAM quotation have been observed in some publications related to DILI.…”
Section: Chinamentioning
confidence: 99%
“…The stilbene component of Polygonum multiflorum improves the function of damaged fatty livers in rats and reduces lipid peroxide contents in the liver. Moreover, P. multiflorum is rich in phospholipids that promote cholesterol and lipids metabolism in the liver, thereby reducing intrahepatic fat accumulation [116,117]. Perhaps further in-depth research will determine whether the aforementioned herbs slow the inflammatory response by regulating Kupffer cells and other macrophages to achieve anti-oxidant and anti-liver fibrosis effects.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%